Identity and Definiteness in Chinese wh-Conditionals - Crain, Stephen; Luo, Qiong-Peng (Proceedings of Sinn und Bedeutung, 2019)
Previous studies of Chinese wh-conditionals leaveseveral issues unresolved, including (i) definiteness effects; (ii) apparent violations of the novelty condition and (iii) accounting for the range of readings of Chinese wh-conditionals. We attempt to resolve some of these issues by analysing wh-indefinites as unique indefinites and wh-conditionals as special instances of topic-comment structures (i.e. wh-conditionals are topic-comment structures with an identity relation). Chinese wh-conditionals can refer to either a single situation or multiple situations, leading to either a definite interpretation or a generic interpretation respectively.